FUNGSI PERENCANAAN PAJAK AGAR TERHINDAR DARI PEMERIKSAAN FISKUS - nk jaya; Wayan Sunia (Jurnal Ilmiah Akuntansi & Bisnis, 2017)
Tax is one of sources of state’s revenue to fill the National Budget (APBN).  The government has the right to impose tax in order to operate a state based on the Law.  One of functions of tax impose is as the “budgeter” which is a tax impose to fill the state’s cash for the development, which is increased every year.  In other hand, revenue other than tax such as oil and gas, coal, mine and other natural resources are decreasing, therefore the revenue of tax is expected to be able to support the National Budget.  The tax collection system (especially the revenue tax (PPh) in Indonesia, it uses the Self Assessment System” which means that the government gives full looseness to taxpayers in carrying out their taxation duty, regarding the counting, paying and report their revenue tax according to the condition of the taxpayers alone.  The nature of the government is supervising, counseling, and building to the consciousness level and the honesty of the taxpayer.  People who have high consciousness and honesty mean they carry out their duties sincerely from themselves without expecting any reward directly for the people who pay it.  For the sake of Indonesian people development.  Even though, the fiscus in its function to build and supervise, it cannot be separated from the action of investigation, in order to test the obedience of taxation obligation fulfillment.  In addition, there are still other purposes for the investigation, which is for the application of objection or appeal, giving of NPWP (in occupation) or the disbandment, to establish PKP or to revoke PKP, comparison of data or information tool, negligence, incompleteness, in performing the taxation obligation is also likely for the investigation action by fiskus. On the other hand the taxpayer want to minimize to pay taxes.  In this discussion what is the tax planning in order to avoid the investigation action. Keyword: The urgency of tax Planning